2017
DOI: 10.5539/ies.v10n7p18
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Experiences and Views on Project-Based Learning Processes

Abstract: Project-based learning (PjBL) has been promoted as an effective and frequently used student-centered learning approach for various learning environments. To have various learning experiences with PjBL is an important requirement for pre-service teachers (PSTs). The purpose of the study was to investigate the experiences PSTs had with group work and collaboration, resources and research methods, the problems they faced, and the strategies they used to overcome these problems during the information and communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…The findings can be seen in Table 6. In this context, it can be said that the findings show similarities with the relevant literature (Dag & Durdu, 2017;Guo et al, 2020;Putri et al, 2017;Torres et al, 2016). Qualitative findings based on three open-ended questions revealed participants' positive, negative opinions and suggestions for implementation of PjBL in online courses.…”
Section: Statements Not True N (%)supporting
confidence: 80%
See 2 more Smart Citations
“…The findings can be seen in Table 6. In this context, it can be said that the findings show similarities with the relevant literature (Dag & Durdu, 2017;Guo et al, 2020;Putri et al, 2017;Torres et al, 2016). Qualitative findings based on three open-ended questions revealed participants' positive, negative opinions and suggestions for implementation of PjBL in online courses.…”
Section: Statements Not True N (%)supporting
confidence: 80%
“…Table 2 shows the frequency and the percentage of each statement regarding the contribution of the project to group work and collaboration skills. According to the first statement, 86% of the students stated that it contributed to the development of group working skills, which is a high ratio compared to those who said no (11%) and which is a similar finding in the literature (Dağ &Durdu, 2012;Dag & Durdu, 2017;Putri et al, 2017;Shin, 2018). Similarly, most of the participants (76%) believed the project also contributed to their collaborative working skills and they stated they mostly had good communication as a group.…”
Section: Findings and Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Several studies that deal with the educational technology that discusses the preparation of the technology have found that technology-based teaching method for the purpose of presentation, of digital content display such as video and online sources, and of discussion over the specific representations on certain subjects has been consistent with the efforts of implementing the technology in the teachers' educational program (McGrail et al, 2011). In addition, critical-thinking and problem-solving are necessary in establishing competencies under the objective of ensuring that the objective of an education system is to learn and not to teacher (Dag & Durdu, 2017).…”
Section: Identification Of the Web-based Inquirymentioning
confidence: 84%
“…Most students' opinion was positive towards the achievement of content knowledge, interdisciplinary skills, and the use of PjBL in their courses [9] The project-based learning model affects the students creative thinking ability [10]. Studies have proven that when implemented well, project-based learning results positive outcomes related to students' learning in the areas of content knowledge, collaborative skills, engagement and motivation, and critical thinking and problemsolving skills [11] Project-based learning (PjBL) has been promoted as an effective and frequently used student-centered learning approach for various learning environments [12]. The PjBL alse enchances the cognitive and critical thinking.…”
Section: Introductionmentioning
confidence: 99%